Accelerated partial breast irradiation with external beam radiotherapy : First results of the German phase 2 trial - Ott, Oliver J.; Strnad, Vratislav; Stillkrieg, Wilhelm; Uter, Wolfgang; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND AND PURPOSE: To evaluate the feasibility and efficacy of external beam three-dimensional (3D) conformal accelerated partial breast irradiation (APBI) for selected patients with early breast cancer. PATIENTS AND METHODS: Between 2011 and 2016, 72 patients were recruited for this prospective phase 2 trial. Patients were eligible for APBI if they had histologically confirmed breast cancer or pure ductal carcinoma in situ (DCIS), a tumor diameter ≤3 cm, clear resection margins ≥2 mm, no axillary lymph node involvement, no distant metastases, tumor bed clips, and were aged ≥50 years. Patients were excluded if mammography showed a multicentric invasive growth pattern, or if they had residual diffuse microcalcifications postoperatively, an extensive intraductal component, or vessel invasion. Patients received 3D conformal external beam APBI with a total dose of 38 Gy in 10 fractions in 1-2 weeks. The trial had been registered at the German Clinical Trials Register, DRKS-ID: DRKS00004417. RESULTS: Median follow-up was 25.5 months (range 1-61 months). Local control was maintained in 71 of 72 patients. The 3‑year local recurrence rate was 2.1% (95% confidence interval, CI: 0-6.1%). Early toxicity (grade 1 radiodermatitis) was seen in 34.7% (25/72). Late side effects ≥ grade 3 did not occur. Cosmetic results were rated as excellent/good in 96.7% (59/61). CONCLUSION: APBI with external beam radiotherapy techniques is feasible with low toxicity and, according to the results of the present and other studies, on the way to becoming a standard treatment option for a selected subgroup of patients.
EVALuna2:32915